C-terminal and intact FGF23 in kidney transplant recipients and their associations with overall graft survival - Chu, Chang; Elitok, Saban; Zeng, Shufei; Xiong, Yingquan; Hocher, Carl-Friedrich; Hasan, Ahmed A.; Krämer, Bernhard; Hocher, Berthold (BMC nephrology, 2021)
Increased fibroblast growth factor 23 (FGF23) is a risk factor for mortality, cardiovascular disease, and progression of chronic kidney disease. Limited data exist comparing the association of either c-terminal FGF23 (cFGF23) or intact FGF23 (iFGF23) in kidney transplant recipients (KTRs) with overall (all-cause) graft loss.
Gesehen am 12.07.2021